PENGARUH PENGGUNAAN PUZZLE JAM TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI PAUD TERPADU HARAPAN NEGERI KECAMATAN BUNGARAYA KABUPATEN SIAK - Novita, Wiwi; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of the use of clock puzzles on the ability to recognize the concept of numbers in children aged 5-6 years in the Early Childhood School of Hope District Bungaraya Siak district. The research used experimental method with one group pre-test post-test design. The sample used in this study were 15 students. The data collection technique used is observation. Technique of data analysis using t-test test by using program of SPSS 17. The research hypothesis is that there is influence of the use of puzzle clock to the ability to recognize the concept of number in children aged 5-6 years in the Early Childhood Education of Hope of the District of Bungaraya district Siak. Based on data analysis known thitung = 23,082> ttabel = 1,746 with Sig. (2-tailed) = 0,000. Because Sig <0,05 it can be concluded that there are differences of interpersonal intelligence before and after given treatment with the clock puzzle. It can be interpreted that there is influence of giving treatment by using puzzle hours to the ability to recognize the concept of numbers in children aged 5-6 years in Paud Terpadu Harapan Negeri Bungaraya subdistrict Siak regency which his significant at 67.52%. Keywords: Concept of Numbers, Puzzle Clock